2007
DOI: 10.3233/isu-2006-26404
|View full text |Cite
|
Sign up to set email alerts
|

Science indicators revisited – Science Citation Index versus SCOPUS: A bibliometric comparison of both citation databases

Abstract: Although the evaluation of knowledge in the form of a quantitation of scientific output is not uncontroversial, it is a widely practised form of science evaluation. For more than 30 years, the Science Citation Index (SCI) has been alone in fulfilling mis purpose. But since 2005 Scopus is a direct competitor to the SCI-databases. Comparing the two databases should help to answer questions that could have repercussions for the future generation of bibliometric analyses. The results of the comparison will allow u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 2 publications
1
40
0
7
Order By: Relevance
“…Our assumption is that the top citing journals and conference proceedings are the most important channels of scholarly communication in a given domain and, therefore, it is expected that these journals and conference proceedings are being indexed in citation databases. This assumption is actually one of the main criteria for journal selection in Web of Science (Ball & Tunger, 2006;Testa, 2004).…”
Section: N=6919 (93%)mentioning
confidence: 99%
“…Our assumption is that the top citing journals and conference proceedings are the most important channels of scholarly communication in a given domain and, therefore, it is expected that these journals and conference proceedings are being indexed in citation databases. This assumption is actually one of the main criteria for journal selection in Web of Science (Ball & Tunger, 2006;Testa, 2004).…”
Section: N=6919 (93%)mentioning
confidence: 99%
“…For each of twenty-one keywords used, Scopus retrieved the larger number of relevant articles. There is evidence that Scopus, in its journal coverage, largely practises the quantity/breadth principle whereas WoS is more orientated towards quality/depth (Ball & Tunger 2006). In the abovementioned study of oncology journals (López-Illescas, De Moya-Anegón & Moed 2008), for instance, an analysis of the additional (non-WoS) journals in Scopus showed that many of these were low-impact journals.…”
Section: Scopus Versus Wos: Insights From the Relevant Literaturementioning
confidence: 99%
“…¿Cómo se evalúa la producción científica de las universidades, países y áreas temáticas en un ámbito global? Principalmente, midiendo su producción científica registrada en las bases de datos de referencia (marco común), especialmente Web of Science (Ball y Tunger, 2006;Delgado y Repiso, 2013;Santa y Herrero-Solana, 2010) y Scopus (Burnham, 2006). ¿Por qué Web of Science es un buen objeto de estudio para caracterizar la producción de las universidades?…”
Section: Palavras-chaveunclassified